Examining Escherichia coli glycolytic pathways, catabolite repression, and metabolite channeling using Δpfk mutants. Issue 1 (December 2016) - Hollinshead, Whitney; Rodriguez, Sarah; Martin, Hector; Wang, George; Baidoo, Edward; Sale, Kenneth; Keasling, Jay; Mukhopadhyay, Aindrila; Tang, Yinjie
Abstract Background Glycolysis breakdowns glucose into essential building blocks and ATP/NAD(P)H for the cell, occupying a central role in its growth and bio-production. Among glycolytic pathways, the Entner Doudoroff pathway (EDP) is a more thermodynamically favorable pathway with fewer enzymatic steps than either the Embden–Meyerhof–Parnas pathway (EMPP) or the oxidative pentose phosphate pathway (OPPP). However, Escherichia coli do not use their native EDP for glucose metabolism. Results Overexpression ofedd andeda inE. coli to enhance EDP activity resulted in only a small shift in the flux directed through the EDP ( 20 % of glycolysis flux). Disrupting the EMPP by phosphofructokinase I (pfkA ) knockout increased flux through OPPP ( 60 % of glycolysis flux) and the native EDP ( 14 % of glycolysis flux), while overexpressingedd andeda in this ΔpfkA mutant directed 70 % of glycolytic flux through the EDP. The downregulation of EMPP via thepfkA deletion significantly decreased the growth rate, while EDP overexpression in the ΔpfkA mutant failed to improve its growth rates due to metabolic burden. However, the reorganization ofE. coli glycolytic strategies did reduce glucose catabolite repression. The ΔpfkA mutant in glucose medium was able to cometabolize acetate via the citric acid cycle and gluconeogenesis, while EDP overexpression in the ΔpfkA mutant repressed acetate flux toward gluconeogenesis. Moreover, 13 C-pulse experiments in the ΔpfkA mutants showed unsequential labeling dynamics in glycolysis intermediates, possibly suggesting metabolite channeling (metabolites in glycolysis are pass from enzyme to enzyme without fully equilibrating within the cytosol medium). Conclusions We engineeredE. coli to redistribute its native glycolytic flux. The replacement of EMPP by EDP did not improveE. coli glucose utilization or biomass growth, but alleviated catabolite repression. More importantly, our results supported the hypothesis of channeling in the glycolytic pathways, a potentially overlooked mechanism for regulating glucose catabolism and coutilization of other substrates. The presence of channeling in native pathways, if proven true, would affect synthetic biology applications and metabolic modeling.